(untitled) (Conferencea, 2022)
The article acknowledges that success in the development of national education of students can be achieved only through the effective use of media technology. As noted in the article, a creative environment and advanced pedagogical experience play a special role in the development of creative abilities in students. In our study, a statistical analysis of the results obtained at the initial and final stages is presented. The experiment presents tables consisting of test results and statistical calculations.